Control and localization of rat adrenal cyclic guanosine 3', 5'-monophosphate. Comparison with adrenal cyclic adenosine 3', 5'-monophosphate. - Whitley, T H; Stowe, N W; Ong, S H; ey, R L; Steiner, A L (The Journal of Clinical Investigation, 1975)
Cyclic AMP and cyclic GMP were measured in rat adrenal glands after either hypophysectomy alone or after hypophysectomy and treatment with ACTH. Adrenal cyclic GMP levels rise in acutely hypophysectomized rats to a maximum at 1 h of approximately 200% of control levels; there is a return to base line at 4-12 h after hypophysectomy. In contrast, adrenal cyclic AMP falls immediately to about 50% of control levels after hypophysectomy and remains at approximately 1 pmol per mg tissue. Doses of ACTH beyond the physiological range markedly suppress adrenal cyclic GMP while producing a 50-fold or greater rise in cyclic AMP in hypophysectomized rats. This pattern of adrenal cyclic GMP rise was unchanged in acutely hypophysectomized animals treated with desamethasone. N-6-2'-0 dibutyryl cyclic AMP acted similarly to the effect of ACTH in bringing about a suppression of adrenal cyclic GMP levels. Physiological i.v. pulse doses of ACTH produced a rapid dose related increase in adrenal cyclic GMP. In vitro incubation of quartered adrenal pairs with 500 mU ACTH produced elevated cyclic AMP levels and suppression of cyclic GMP. Whereas adrenal cyclic AMP fell rapidly to 50% of control levels after hypophysectomy and remained at about 1 pmol per mg tissue for 7 days, adrenal cyclic GMP showed a biphasic rhythm in long-term hypophysectomized animals. After an initial peak at 1 h after hypophysectomy, adrenal cyclic GMP declined to baseline at 4-12 h but thereafter progressively rose with time, eventually reaching levels over 1 pmol per mg tissue. Fluorescent immunocytochemical staining of rat adrenal zona fasciculata showed cyclic AMP largely confined to cytoplasmic elements with little fluorescence contained in nuclei. In constant, cyclic GMP was found discretely positioned in nuclei with prominent fluorescence in nucleoli in addition to cytoplasmic localization. It is concluded that in hypophysectomized rats ACTH, either directly or in conjunction with altertion of adrenal cyclic AMP, appears to be one factor which regulates adrenal cyclic GMP. The direction of cyclic GMP change and the different subcellular localization of the nucleotides suggest divergent roles for cyclic AMP and cyclic GMP in adrenocortical function. Furthermore, our observations suggest a role for adrenal cyclic GMP in nuclear directed events. Images